Repeated Mandibular Extension in Rat: A Procedure to Modulate the Cerebral Arteriolar Tone - Lapi, Dominga; Varanini, Maurizio; Colantuoni, Antonio; Del Seppia, Cristina; Ghione, Sergio; Fommei, Enza; Scuri, Rossana (Frontiers in Physiology, 2017)
Previous data have shown both in the rat and in the human that a single mandibular extension lasting 10 minutes induces a significant important and prolonged reduction in blood pressure and heart rate, affecting also rat pial microcirculation by the release of endothelial factors. In the present work, we assessed whether repeated mandibular extension could further prolong these effects. We performed two mandibular extensions, the second mandibular extension being applied 10 minutes after the first one. The second mandibular extension produced a reduction in blood pressure and heart rate for at least 240 minutes. As in the case of a single mandibular extension, pial arterioles dilated for up to 140 minutes after the second extension. Spectral analysis on 30 minutes recordings under baseline conditions and after repeated mandibular extensions showed that the pial arterioles dilation was associated with rhythmic diameter changes sustained by an increase in the frequency components related to endothelial, neurogenic and myogenic activity while a single mandibular extension caused an increase only in the endothelial activity. In conclusion, repeated mandibular extension prolonged the effects of a single mandibular extension on blood pressure, heart rate and vasodilation and induced a modulation of different frequency components responsible of the pial arteriolar tone, in particular increasing the endothelial activity.